A comprehensive welfare scoring system for graft versus host disease clinical assessment in humanised mouse models used for pharmaceutical research - Alice Nowak; Rebecca Marlow; Kelli Ryan; Jean-Martin Lapointe; Daniel Sutton; Alan Sharpe; Lucy Crook; Jennifer A. Walker; Emma Little; John Peverill; Adam Holberry-Brown; Emma Wassell; et al. (Frontiers in Immunology)
Immuno-oncology drug discovery increasingly relies on humanised mouse models of cancer due to limitations of murine surrogate tools and differences between mouse and human immune systems. Graft-versus-Host Disease (GvHD) is a significant complication following xenogeneic transplantation of human immune cells into mice, limiting their lifespan and impacting the utility of these studies. Existing GvHD scoring systems inadequately capture the disease’s complexity, hampering optimal welfare management and clinical progression monitoring. We propose a comprehensive, practical scoring system for monitoring clinical signs of GvHD in humanised mice. It evaluates seven clinical signs reflecting disease complexity, sums the scores, and categorises overall GvHD severity into four stages, each with specific welfare actions. This refined tool reduces animal suffering through early detection and timely interventions, enabling mice to remain on studies where possible to maximise scientific impact. Our scoring system correlates with histological scores of GvHD-induced tissue damage across multiple organs, with liver and kidney histopathology ranking highly, unlike lung pathology. The system is reproducible among independent experimenters and versatile, effectively applied across multiple types of humanised mouse models and strains. It identifies common clinical signs including weight loss, swelling/reddening of extremities, fur condition, and posture changes, aiding users in distinguishing relevant signs. This system refines and standardises welfare decision-making, supporting the responsibility to minimise suffering when working with humanised mice.